2020
DOI: 10.24198/pjd.vol32no1.25486
|View full text |Cite
|
Sign up to set email alerts
|

Formulation of mouth rinse from the essential oils of lime (Citrus aurantifolia) and its inhibitory efficacy on the growth of Streptococcus mutans – in vitro

Abstract: Introduction: Essentials oil of lime (Citrus aurantifolia) peel has high activity in inhibiting the growth of Streptococcus mutans bacteria. The objective of this research was to determine the formulation of mouth rinse from the essential oils of lime (C. aurantifolia) with the highest inhibitory and on the growth of S. mutans. Methods: This research was an experimental in-vitro study. The sample used was the lime (C. aurantifolia) peel waste peel using hydrodistillation technique; testing of the essential oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Mekanisme kerja tanin sebagai antibakteri yaitu menghambat enzim reverse transkriptase dan DNA topoisomerase sehingga sel bakteri tidak dapat terbentuk. 27,28 Kandungan dari daun singkong yang berperan dalam antiinflamasi dan antibakteri ini menyebabkan sel-sel inflamasi yang bermigrasi menjadi terbatas, ekspresi MMP-8 dapat ditekan, dan tanda-tanda klinis peradangan pun berkurang. Dengan demikian, ekstrak daun singkong ini efektif menurunkan ekspresi MMP-8 sehingga tidak menyebabkan degradasi kolagen yang lebih besar dan dapat menekan gejala klinis periodontitis.…”
Section: Pembahasanunclassified
“…Mekanisme kerja tanin sebagai antibakteri yaitu menghambat enzim reverse transkriptase dan DNA topoisomerase sehingga sel bakteri tidak dapat terbentuk. 27,28 Kandungan dari daun singkong yang berperan dalam antiinflamasi dan antibakteri ini menyebabkan sel-sel inflamasi yang bermigrasi menjadi terbatas, ekspresi MMP-8 dapat ditekan, dan tanda-tanda klinis peradangan pun berkurang. Dengan demikian, ekstrak daun singkong ini efektif menurunkan ekspresi MMP-8 sehingga tidak menyebabkan degradasi kolagen yang lebih besar dan dapat menekan gejala klinis periodontitis.…”
Section: Pembahasanunclassified
“…It was reported that the peel of C. aurantifolia comprise of various benefits such as antibacterial effect. 11 Pavithra et al (2009) reported the active compounds that responsible as antibacterial in Citrus peels oil, encompassing the monoterpenes component. 12 The essential oils generated from C. aurantifolia have been applied in mouthwash and showed the ability to inhibit S. mutans growth.…”
Section: Introductionmentioning
confidence: 99%
“…Modern society nowadays realises that natural-based mouth rinse, such as lime peel essential oil-based mouth rinse is relatively safer to use for a long term period on a daily basis. 10 Calendula officinalis is the experimental sample in this study, is widely cultivated as a herb it is a remarkable healing agent and even useful to act as homeopathic remedies. Its extract has been used in Europe since before the 12 th century primarily as a topical antiinflammatory agent.…”
Section: Introductionmentioning
confidence: 99%